Sustained complete molecular remission after imatinib discontinuation in children with chronic myeloid leukemia. Issue 11 (9th May 2014) - Moser, Olga; Krumbholz, Manuela; Thiede, Christian; Tauer, Josephine T.; Janz, Indra; Lauten, Melchior; Dilloo, Dagmar; Metzler, Markus; Suttorp, Meinolf
<x xml:space="preserve">Abstract</x> Approximately 40% of adults with chronic myeloid leukemia (CML) in prolonged complete molecular response (CMR) remain in CMR after imatinib discontinuation. Corresponding information in children is lacking. Two children with CML in CMR for 48 and 19 months after imatinib discontinuation showed low‐level fluctuating disease at RNA transcript and genomic DNA levels. Both patients were low risk according to adult criteria. Since adults with molecular relapse responded to re‐introduction of imatinib, we postulated that treatment discontinuation in low risk children might be justified within clinical trials with close monitoring. This may help to minimize exposure to imatinib and its potential side effects. Pediatr Blood Cancer 2014;61:2080–2082. © 2014 Wiley Periodicals, Inc.